Determinants of Consumers' Willingness-to-pay for Fairly-produced, Locally Grown Dairy Products - Agnes Emberger-Klein; Klaus Menrad; Dominik Heider (German Journal of Agricultural Economics (GJAE), 2016)
At the end of the last decade, several regional marketing projects were launched in the dairy sectors of various Alpine countries with the aim of creating a higher added value for milk products and allowing fair prices for the dairy farmers involved. The projects wanted to offer an alternative marketing channel for the farms in these regions by marketing 'fairly-produced, locally grown products'. The aim of this study is to analyze the determinants of consumers' willingness-to-pay (WTP) for fairly-produced, locally grown products using two different WTP measures: the first one describes a more general willingness-to-pay (WTPGEN) and the second one quantifies the price premium (WTPQUAN) respondents are willing to pay. The influence of both person-related and environmental factors, which are known to have an impact on food-related consumption behavior, was determined introducing and using the Shapley value (SV) decomposition of R2. This concept is commonly used in the commercial marketing context, but until now it has rarely been applied in academic research on food-related consumption behavior, even though it provides interesting advantages. The results show that consumers' WTP for fairly-produced, locally grown products is influenced by person-related factors as well as by environmental factors. In the case of WTPQUAN, a dominant influence by consumers' price consciousness can be observed, while a higher relative importance of the more global constructs of norms, stated preferences, and values can be detected when ex-plaining WTPGEN.
Keywords: 330